(untitled) (INNOTEC, 2017)
Some arthropod groups are considered to be good bioindicators of environmental quality. For that, they must fill some conditions, such as biological and morphological characteristics that lead to their easy find and identification. The pit-fall traps are widely used as an efficient method to collect predator arthropods that may have a good potential as bioindicators of the characteristics of their environment. During a nine months period, fortnightly collects were made in three production systems with different intensity of anthropic intervention, in the Laguna Negra basin, Rocha, Uruguay: natural grassland with low intensity of bovine cattle grazing; bovine and sheep grazed area, and an area under high bovine grazing intensity with winter-summer agriculture. In each of the three areas two series of 10 pitfall traps were installed with a distance 100 m minimum between series and 10 m between traps. Two spider morphospecies, Mesabolivar sp (Pholcidae) y Steatoda sp (Theridiidae) appeared to be good indicators for the less and most intensified environments, respectively. Other four morphospecies of the families Nemesiidae, Oxyopidae, Lycosidae y Palpimanidae were characterized as detectors to different environments. Four morphospecies of the coleopteran family Carabidae (Calosoma retusum, Galerita collaris, Brachinus sp and Pelecium sp) were defined as indicators of the more intensified system, with agriculture.